Ecological risk assessment of the wetlands in Beijing-Tianjin-Hebei urban agglomeration. (October 2020) - Li, Zhuo; Jiang, Weiguo; Wang, Wenjie; Chen, Zheng; Ling, Ziyan; Lv, Jinxia
Graphical abstract: Highlights: Wetland ecological risk is related to external hazard and internal vulnerability. An index system consisting of 22 indexes was founded from hazard and vulnerability. The changes of wetland ecological risk in 181 counties were quantitatively evaluated. Protection policies have played a substantial role in wetland restoration. Abstract: Wetlands are some of the most highly productive ecosystems on earth and are one of the most important environments for human survival and development. However, with the acceleration of industrialization and urbanization, wetlands have been constantly occupied and destroyed and have even disappeared in some areas, so it is necessary to establish a reasonable and scientific ecological risk assessment system for wetlands. In this study, 181 counties in Beijing-Tianjin-Hebei urban agglomeration (Jing-Jin-Ji) were selected as the research objects, and an index system with 22 indexes was established from two aspects: the external hazard degree and the vulnerability of the wetland itself. The ecological risk of the wetlands during 6 periods from 1990 to 2015 was comprehensively evaluated by long-term data and multiple index factors. The results showed that (1) due to the decrease in the hazard degree and the increase in the vulnerability, the ecological risk of the wetlands in Jing-Jin-Ji first increased and then decreased; (2) more than 60% of the counties were at the middle or middle-high risk level, especially in the center of urban development, which generally had higher risk level than other regions; (3) most wetland parks were at the middle-high risk level, while wetland reserves, reservoirs and lakes were mostly in the low risk or middle-low risk level. Therefore, in recent years, the implementation of wetland protections and restoration policies and projects has played a significant role in reducing the ecological risk of the wetlands. In the future, more targeted management and protection measures need to be formulated and followed up in time.